2020
DOI: 10.1002/cctc.202000662
|View full text |Cite
|
Sign up to set email alerts
|

1,3,2‐Diazaphospholenes Catalyze the Conjugate Reduction of Substituted Acrylic Acids

Abstract: The potent nucleophilicity and remarkably low basicity of 1,3,2‐diazaphospholenes (DAPs) is exploited in a catalytic, metal‐free 1,4‐reduction of free α,β‐unsaturated carboxylic acids. Notably, the reduction occurs without a prior deprotonation of the carboxylic acid moiety and hence does not consume an additional hydride equivalent. This highlights the excellent nucleophilic character and low basicity of DAP‐hydrides. Functional groups such as Cbz group or alkyl halides which can be problematic with classical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…Building on our previous work 59 , we envisioned that diazaphospholenes of super hydricity 60 62 may provide a good chance to realize HDF of trifluoromethylalkenes via an S N 2’ path 63 . A preliminary attempt indicated that the reaction of α-trifluoromethyl-styrene 2a with diazaphospholene 1 primarily gave the hydrophosphination intermediate A .…”
Section: Resultsmentioning
confidence: 98%
“…Building on our previous work 59 , we envisioned that diazaphospholenes of super hydricity 60 62 may provide a good chance to realize HDF of trifluoromethylalkenes via an S N 2’ path 63 . A preliminary attempt indicated that the reaction of α-trifluoromethyl-styrene 2a with diazaphospholene 1 primarily gave the hydrophosphination intermediate A .…”
Section: Resultsmentioning
confidence: 98%
“…Another plausible pathway is the 1,4-addition pathway. According to whether the P atom of the 1,3,2-diazaphospholene (DAP) moiety is connected to the C1 or O4 atom, the 1,4-addition can be divided into two types, 1,4-addition (PC) and 1,4-addition (PO) pathways. In the 1,4-addition (PC) pathway, 3 approaches allyl 2-phenylacrylate 4 to form compound 5 PC with an association energy of −2.9 kcal/mol (blue lines in Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…The potent nucleophilic properties of DAP-hydrides, and their remarkably low basicity, was recently exploited by the Cramer group who showed that the combination of DAP-precatalyst 38 and phenylsilane (PhSiH 3 ) as the terminal reductant can effect the selective 1,4-reduction of α,β-unsaturated carboxylic acids (Scheme 15). 29 Despite the presence of the potentially problematic acidic proton, the reaction smoothly proceeds to completion with only 0.35 equivalents of PhSiH 3 , demonstrating that each hydride on the stoichiometric reducing agent is competent for catalyst turnover, and that any acid-base reactivity is virtually negligible under the reaction conditions and is dominated by the nucleophilic delivery of hydride to the β-position of the substrate. A wide variety of functional groups were well tolerated in the reaction, and when the chiral DAP 29 was employed with pinacol borane as the terminal reductant, 2-phenylpropionic acid was obtained with moderate enantioenrichment (64 : 36 er).…”
Section: Conjugate Reductions Of αβ-Unsaturated Carbonyl Compoundsmentioning
confidence: 98%
“…First generation chiral scaffolds have been based around commercially-available chiral amines, giving quick and efficient access to the targeted DAPs 13-18. 22,23 Subsequent chiral DAPs have employed annulated chiral manifolds to give more rigid DAP structures with conformationally locked stereochemical environments (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). 20,24 The methodologies (both racemic and enantioselective) in which these catalysts and precatalysts have been utilized will now be systematically discussed.…”
Section: Catalytic Reactionsmentioning
confidence: 99%